2002
DOI: 10.1136/vr.151.22.658
|View full text |Cite
|
Sign up to set email alerts
|

Study of crib‐biting and gastric inflammation and ulceration in young horses

Abstract: Nineteen young horses that had recently started to perform the stereotypy of crib-biting were compared with 16 non-stereotypic horses for 14 weeks. After initial observations of their behaviour and an endoscopic examination of the condition of their stomachs, the horses were randomly allocated to a control or an antacid diet At the start of the trial, the stomachs of the crib-biting foals were significantly more ulcerated and inflamed than the stomachs of the normal foals. In addition, the faecal pH of the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 16 publications
2
77
0
6
Order By: Relevance
“…Gastric ulcers have been loosely associated with a range of clinical signs in adult horses, despite a paucity of strong epidemiological evidence to support these associations. Reported clinical signs include poor appetite or ‘picky eating’,7, 11, 33, 34 poor body condition, or weight loss,9, 11, 33 chronic diarrhea,11, 33 poor coat condition,7 bruxism,35 behavioral changes (including an aggressive or nervous disposition),12, 33, 36 acute or recurrent colic7, 11, 33, 37, 38, 39, and poor performance 7, 10, 33, 40, 41…”
Section: Clinical Signsmentioning
confidence: 99%
“…Gastric ulcers have been loosely associated with a range of clinical signs in adult horses, despite a paucity of strong epidemiological evidence to support these associations. Reported clinical signs include poor appetite or ‘picky eating’,7, 11, 33, 34 poor body condition, or weight loss,9, 11, 33 chronic diarrhea,11, 33 poor coat condition,7 bruxism,35 behavioral changes (including an aggressive or nervous disposition),12, 33, 36 acute or recurrent colic7, 11, 33, 37, 38, 39, and poor performance 7, 10, 33, 40, 41…”
Section: Clinical Signsmentioning
confidence: 99%
“…Conversely, domestic/captive horses daily receive a limited number of high energy meals and a limited amount of roughage (e.g. Harris, 2005;Nicol et al, 2002). When domestic horses are placed as a group in a bare paddock and given a variety of enrichments including straw, branches, object, they showed a time limited interest in objects and the only efficient enrichment appeared to be the straw (providing thus foraging opportunity) (Jorgensen et al, 2011).…”
Section: Resources Availabilitymentioning
confidence: 99%
“…Reward behaviour has been connected as a causal factor with crib-biting (Nicol et al, 2002;Hemmings et al, 2007). The plasma leptin concentration was lower in crib-biting horses compared with controls and correlated negatively with crib-biting intensity during feeding .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic evidence in other animal stereotypies has been established, including examples such as bank voles (Schoenecker and Heller, 2000) and compulsive dogs (Dodman et al, 2010). Stress, gastric discomfort and frustration caused by stall restrictions and early weaning (Nicol et al, 2002;Latham and Mason, 2008;Hothersall and Nicol, 2009) have been suggested as additional risk factors for equine crib-biting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation